2012
DOI: 10.1080/19338244.2011.578681
|View full text |Cite
|
Sign up to set email alerts
|

Chest Imaging and Lung Function Impairment After Long-Term Occupational Exposure to Low Concentrations of Chrysotile

Abstract: The aim of the present study was the investigation of radiographic findings in relation to lung function after occupational exposure to permissible levels of relatively pure chrysotile (0.5-3% amphiboles). We studied 266 out of the total 317 employees who have worked in an asbestos cement factory during the period 1968-2004 with chest x-ray, high-resolution computed tomography (HRCT) and lung function tests. Sensitivity of chest x-ray was 43% compared to HRCT. Abnormal HRCT findings were found in 75 subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This imprecision has led to considerable debate regarding the pathogenicity of different fiber types (Gwinn, 2011; Gwinn et al, 2011; Lenters et al, 2011). While the debate is not completely resolved, current studies continue to support the contention that at least for extended exposures, chrysotile has the ability to induce both cancer and pulmonary/pleural fibrosis (Spyratos et al, 2012; van der Bij et al, 2013; Wang et al, 2013). There is, however, quite a bit of evidence that, at similar exposures, amphibole asbestos is more pathogenic, especially in terms of scarring of the lung parenchyma and pleura (Donaldson et al, 2010; Mossman et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…This imprecision has led to considerable debate regarding the pathogenicity of different fiber types (Gwinn, 2011; Gwinn et al, 2011; Lenters et al, 2011). While the debate is not completely resolved, current studies continue to support the contention that at least for extended exposures, chrysotile has the ability to induce both cancer and pulmonary/pleural fibrosis (Spyratos et al, 2012; van der Bij et al, 2013; Wang et al, 2013). There is, however, quite a bit of evidence that, at similar exposures, amphibole asbestos is more pathogenic, especially in terms of scarring of the lung parenchyma and pleura (Donaldson et al, 2010; Mossman et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Only two of the studies ( Clin et al, 2011 ; Rui et al, 2004 ) adjusted for BMI in their statistical evaluations. Adjustment for smoking was more common (10 studies), while five ( Clark et al, 2014 ; Clin et al, 2011 ; Rui et al, 2004 ; Spyratos et al, 2012 ; Van Cleemput et al, 2001 ) included adjustments for asbestos exposure ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In one of the two higher quality HRCT studies that adjusted for confounders, Spyratos et al (2012) found that, while FVC and FEV 1 were lower in those with pleural plaques ( n = 29) than those with no abnormalities ( n = 37), when results were adjusted for age, smoking, and duration of asbestos exposure, FVC and FEV 1 were non-statistically increased in individuals with pleural plaques. In the other, Rui et al (2004) found non-significant slight decreases in lung function over time in people with pleural plaques compared to people without.…”
Section: Discussionmentioning
confidence: 99%
“…HRCT[ 24 25 26 27 28 29 30 31 32 ] has been evaluated for screening of nonmalignant asbestos-induced lung disease and is considered to be a more sensitive tool. The recent literature has also documented that chest HRCT findings significantly correlate with pulmonary function and mortality.…”
Section: Discussionmentioning
confidence: 99%